STUDI MUTU PELAYANAN KESEHATAN PASIEN RAWAT INAP PESERTA BPJS DI RUMAH SAKIT UMUM DAERAH KOTA PADANGSIDIMPUAN - Ahmad Safii Hasibuan (Jurnal Komunitas Kesehatan Masyarakat, 2020)
Complaints about health services in hospitals are often heard from participants of health insurance as a sufficient part of meaning sometimes health services that are found to be less satisfactory are usually targeted are the attitude or actions that are not good doctor or paramedics, inadequate facilities, medical supplies, and patient safety and others. The purpose of this study was to determine the description of the quality of inpatient BPJS inpatient health care providers in the Padangsidimpuan City Regional General Hospital. This research was conducted at Padangsidimpuan City Regional General Hospital. This type of research is a survey with a descriptive approach. The sample of this study was inpatients BPJS participants with purposive sampling with a total of 50 samples. The results showed that BPJS inpatients who stated good doctor services with good quality health services were 77.3%, BPJS inpatients who stated good nurse services with good health service quality were 79.5%, inpatients were participants BPJS who stated good patient safety services with good quality health services were 93.9%, inpatients BPJS participants who stated good administrative services with good quality health services were 88.2%. The conclusion is that inpatients BPJS participants stated that good doctor services, good nurse services, good patient safety services, good administration with good quality health services. In terms of doctor, nurse, patient safety and administration services, it is expected that in examining patients it should be given time for each patient so that patients do not consider the examination to be rushed.